A novel class of supercoil-independent nuclease hypersensitive site is comprised of alternative DNA structures that flank eukaryotic genes. - Vernick, K.D.; McCutchan, T.F. (Journal of Molecular Biology, 1998)
The cell makes a fundamental distinction between genes and non-gene sequences, which mechanistically underlies the process of gene regulation. Here, we describe the properties of a novel class of genetic sites that reproducibly flank and delineate the coding regions of the eukaryotic genes tested. Defined in vitro reaction conditions that include altered solvation and elevated temperature rendered the sites hypersensitive to nuclease cleavage. Consequently, the complete coding regions of the Drosophila genes tested were quantitatively excised from genomic DNA or genomic clones by this treatment. Identical reaction products were generated from linear or supercoiled DNA substrates. Chemical modification and fine-structure analysis of several cleavage sites flanking Drosophila genes showed that the cleavage sites were stable nucleic acid structures that contained specific arrangements of paired and unpaired nucleotides. The locations and properties of the cleavage sites did not correspond to previously known nuclease hypersensitive sites nor to known alternative DNA structures. Thus, they appear to represent a new class of genetic site. In a deletion analysis, the minimal sequence information necessary to direct in vitro nuclease cleavage 3' to the Drosophila GART gene co-localized with the signal required for termination of transcription in vivo. The data suggest that a novel class of DNA site with distinct structural properties encodes biological information by marking the boundaries of at least some gene expression units in organisms as diverse as Plasmodium and Drosophila.